2021
DOI: 10.3390/jcm10020335
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Myocardial Strain Using Cardiac Magnetic Resonance in Patients with Wilson’s Disease

Abstract: (1) Background: Wilson’s disease (WD) is an inherited autosomal recessive disorder with the excessive deposition of copper into different organs, including the heart. Previous studies showed structural cardiac changes even in patients with no signs of heart failure. The aim of this study was to perform cardiac magnetic resonance-based strain analysis in WD patients, as it is a powerful independent predictor of mortality. (2) Methods: We conducted a prospective cardiac magnetic resonance study that included 61 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 29 publications
0
1
0
Order By: Relevance
“…In our study, no significant difference was observed in 2D LV-Strain (GRS, GCS, GLS) between the WD and control groups, which was inconsistent with previous studies [6,8]. In the studies of Salatzki et al [6] and Zhang et al [8], LV-GRS and LV-GCS in WD patients were significantly lower than those in controls. This difference may be due to the younger patients in our study and the shorter duration of copper exposure.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…In our study, no significant difference was observed in 2D LV-Strain (GRS, GCS, GLS) between the WD and control groups, which was inconsistent with previous studies [6,8]. In the studies of Salatzki et al [6] and Zhang et al [8], LV-GRS and LV-GCS in WD patients were significantly lower than those in controls. This difference may be due to the younger patients in our study and the shorter duration of copper exposure.…”
Section: Discussioncontrasting
confidence: 99%
“…ECG abnormalities were found in 19 patients, including premature ventricular contractions (n = 4), sinus bradycardia (n = 11), and sinus arrhythmia (n = 4). The median UWDRS score of WD-neuro + patients was 6.0 (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11).…”
Section: Baseline Characteristicsmentioning
confidence: 97%
See 1 more Smart Citation
“…Therefore, in the diagnosis and the follow-up of WD patients, tests such as electrocardiogram, cardiac biomarkers, echocardiography, and 24-h Holter monitoring should be included [27]. By cardiac magnetic resonance-based strain analysis, a functional impairment of both ventricles was detected in 4 out of 61 WD patients, which may be helpful as a potential early sign of cardiac manifestation [28].…”
Section: Additional Clinical Manifestationsmentioning
confidence: 99%